Alterations in chromosomal genes nfsA, nfsB, and ribE are associated with nitrofurantoin resistance in Escherichia coli from the United Kingdom. Issue 12 (3rd December 2021) - Wan, Yu; Mills, Ewurabena; Leung, Rhoda C.Y.; Vieira, Ana; Zhi, Xiangyun; Croucher, Nicholas J.; Woodford, Neil; Jauneikaite, Elita; Ellington, Matthew J.; Sriskandan, Shiranee
Abstract : Antimicrobial resistance in enteric or urinary Escherichia coli is a risk factor for invasive E. coli infections. Due to widespread trimethoprim resistance amongst urinary E. coli and increased bacteraemia incidence, a national recommendation to prescribe nitrofurantoin for uncomplicated urinary tract infection was made in 2014. Nitrofurantoin resistance is reported in <6% urinary E. coli isolates in the UK, however, mechanisms underpinning nitrofurantoin resistance in these isolates remain unknown. This study aimed to identify the genetic basis of nitrofurantoin resistance in urinary E. coli isolates collected from north west London and then elucidate resistance-associated genetic alterations in available UK E. coli genomes. As a result, an algorithm was developed to predict nitrofurantoin susceptibility. Deleterious mutations and gene-inactivating insertion sequences in chromosomal nitroreductase genes nfsA and/or nfsB were identified in genomes of nine confirmed nitrofurantoin-resistant urinary E. coli isolates and additional 11 E. coli isolates that were highlighted by the prediction algorithm and subsequently validated to be nitrofurantoin-resistant. Eight categories of allelic changes in nfsA, nfsB, and the associated gene ribE were detected in 12412 E. coli genomes from the UK. Evolutionary analysis of these three genes revealed homoplasic mutations and explained the previously reported order of stepwise mutations. The mobile gene complex oqxAB, which is associated with reduced nitrofurantoin susceptibility, was identified in only one of the 12412 genomes. In conclusion, mutations and insertion sequences in nfsA and nfsB were leading causes of nitrofurantoin resistance in UK E. coli . As nitrofurantoin exposure increases in human populations, the prevalence of nitrofurantoin resistance in carriage E. coli isolates and those from urinary and bloodstream infections should be monitored.